High Expression of MUC5AC, MUC5B, and Layilin Plays an Essential Role in Prediction in the Development of Plastic Bronchitis Caused by MPP - Ma, Yu; Gu, Yeqi; Zhang, Xinxing; Gu, Wenjing; Wang, Ting; Sun, Huiming; Dai, Yinfang; Yan, Yongdong; Wang, Yuqing; Wang, Meijuan; Sun, Huiquan; Hao, Chuangli; et al. (Frontiers in Microbiology, 2022)
Plastic bronchitis (PB) is a rare respiratory condition which can result in severe respiratory complication such as respiratory failure and death. Mycoplasma pneumoniae infection is a main etiology cause of plastic bronchitis. However, the pathogenesis of plastic bronchitis complicated by Mycoplasma pneumoniae pneumonia (MPP) has not yet been fully elucidated. Our article aims to explore biomarker for early prediction of MPP cases complicated with plastic bronchitis. We utilized protein chip to screen for significantly different proteins among the group of healthy, General Mycoplasma pneumoniae pneumonia (GMPP) and Refractory Mycoplasma pneumoniae pneumonia (RMPP). layilin exhibit potent change across biology information technology. Next, we demonstrated that the high expression of MUC5AC, MUC5B and layilin in bronchoalveolar lavage fluid (BALF) of MPP cases complicated with plastic bronchitis. Further study suggested that the level of layilin both had positive correlation with MUC5AC, MUC5B. A receiver-operating characteristic (ROC) analysis was performed to assess the diagnostic values of MUC5AC, MUC5B and layilin in MPP cases with PB. Data shows the three indicators have the similar diagnostic ability for MPP children with plastic bronchitis. Then, we use different concentrations of CARDS toxin or Lipid-associated membrane proteins (LAMPs) to simulate in vitro experiment. In vitro assay revealed that CARDS toxin or LAMPS induced A549 cells to secrete MUC5AC, MUC5B, layilin and proinflammatory factors. These findings suggest that MUC5AC, MUC5B, layilin are correlated with MPP. The high expression of MUC5AC, MUC5B, layilin play essential role for prediction in the development of plastic bronchitis caused by MPP. The high expression of MUC5AC, MUC5B, layilin may relevant to the severity of illness.